Tradução para português, adaptação cultural e validação do Female Sexual Function Index Translation into Portuguese, cross-national adaptation and validation of the Female Sexual Function Index - Rosane do Rocio Cordeiro Thiel; Miriam Dambros; Paulo César Rodrigues Palma; Marcelo Thiel; Cássio Luís Zanettini Riccetto; Maria de Fátima Ramos (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2008)
OBJETIVO: traduzir para o português, adaptar culturalmente e validar o questionário Female Sexual Function Index (FSFI). MÉTODOS: dois tradutores brasileiros, cientes dos objetivos desta pesquisa, preparam duas versões do FSFI para o português, as quais foram retro-traduzidas por outros dois tradutores ingleses. As diferenças foram harmonizadas e pré-testadas em um estudo piloto. As versões finais do FSFI e de outro questionário, o Short-Form Health Survey, já vertido e publicado em português, foram simultaneamente administradas a cem pacientes. Foram testadas as propriedades psicométricas do FSFI, como confiabilidade (consistência interna e teste-reteste) e validades de construto. O reteste foi realizado após quatro semanas, a partir da primeira entrevista. RESULTADOS: o processo de adaptação cultural não alterou a versão em português do FSFI comparado ao original. O alfa de Cronbach padronizado do questionário foi 0,96; avaliado por domínios, variou de 0,31 a 0,97. Como medida de confiabilidade teste-reteste, foi aplicado o coeficiente de correlação intra-classes, que foi considerado forte e idêntico (1,0). O coeficiente de correlação de Pearson entre o FSFI e o Short-Form Health Survey foi positivo, mas fraco na maioria dos domínios afins, variando de 0,017 a 0,036. CONCLUSÕES: a versão do FSFI foi traduzida para o português e adaptada culturalmente e é válida para avaliação da resposta sexual das mulheres brasileiras. PURPOSE: to translate from English into Portuguese, adapt culturally and validate the Female Sexual Function Index (FSFI). METHODS: knowing the objectives of this research, two Brazilian translators have prepared a version each from the FSFI into Portuguese. Both versions have then been retro-translated into English by two English translators. After harmonizing the differences, they have been pre-tested in a pilot study. The final versions from the FSFI and from another questionnaire, the Short-Form Health Survey, which had already been translated and published in Portuguese, have then been simultaneously administered to one hundred patients, to test the FSFI psychometric proprieties concerning reliability (internal consistency and testing-retesting) and construct validity. Retesting was done after four weeks from the first interview. RESULTS: the process of cultural adaptation has not altered the Portuguese version of the FSFI, as compared to the original. The FSFI standardized Cronbach alpha was 0.96, and the evaluation by domains has varied from 0.31 to 0.97. As a measure of test-retest confidentiality, it was applied the intra-class coefficient, which has been considered strong and identical (1.0). Pearson's correlation coefficient between the FSFI and the Short-Form Health Survey was positive, but weak in most of the interrelated domains, varying from 0.017 to 0.036. CONCLUSIONS: the FSFI English version has been translated into Portuguese and culturally adapted, being reliable to evaluate the sexual response of Brazilian women.